Inhibition Mechanism of 3-Hydroxyflavones Against α-Glucosidase - Le, Lieu Quang; Nguyen, Luc Tien; Mai, Tan Thanh; Nguyen, Suc Van; Ho, Phuong; Hoang, Hao Minh (Journal of Technical Education Science, 2026)
3-Hydroxyflavones belong to a subgroup of flavonoids that exhibit a broad range of bioactivities. In this respect, diverse 3-hydroxyflavones have been isolated from natural sources and synthesized in laboratories through different chemical routes to search for analogs with promising bioactivities. As part of our ongoing research into the α-glucosidase inhibition of synthesized 3-hydroxyflavones, we herein screened for the α-glucosidase inhibitory activity of 3-hydroxyflavones. Among the tested compounds (1-5), for the first time, two fluorinated derivatives (compounds 4 and 5), bearing fluoro substituents at the 4′- and 3′,4′-positions of the B ring were active, presenting IC50 values of 326.47±0.79 µM and 373.74±1.83 µM, respectively. The intrinsic fluorescence spectra of α-glucosidase were quenched gradually with increasing amounts of inhibitors 4 and 5, indicating both inhibitors were bound to α-glucosidase. Furthermore, when 8-anilino-1-naphthalenesulfonic acid (ANS), an extrinsic fluorescence probe was added to the enzyme solution, the fluorescence intensity of [α-glucosidase-ANS] complex was reduced, suggesting that 3-hydroxyflavone 4 and 5 interacted with the enzyme via hydrophobic domain. Finally, inhibitory kinetic analysis using Lineweaver-Burk plots was also applied for both selected inhibitors. It was found that compounds 4 and 5 acted as competitive inhibitors of α-glucosidase.